Addressing barriers to the prevention, diagnosis and treatment of hepatitis B and C in the face of persisting fiscal constraints in Europe: report from a high level conference. (February 2016) - Papatheodoridis, G.; Thomas, H. C.; Golna, C.; Bernardi, M.; Carballo, M.; Cornberg, M.; Dalekos, G.; Degertekin, B.; Dourakis, S.; Flisiak, R.; Goldberg, D.; Gore, C.; et al.
Summary: In the WHO–EURO region, around 28 million people are currently living with chronic viral hepatitis, and 120 000 people die every year because of it. Lack of awareness and understanding combined with the social stigma and discrimination exacerbate barriers related to access to prevention, diagnosis and treatment services for those most in need. In addition, the persisting economic crisis has impacted on public health spending, thus posing challenges on the sustainable investment in promotion, primary and secondary prevention, diagnosis and treatment of viral hepatitis across European countries. The Hepatitis B and C Public Policy Association in cooperation with the Hellenic Center for Disease Prevention and Control together with 10 partner organizations discussed at the Athens High Level Meeting held in June 2014 recent policy developments, persisting and emerging challenges related to the prevention and management of viral hepatitis and the need for a de minimis framework of urgent priorities for action, reflected in a Call to Action (Appendix S1). The discussion confirmed that persisting barriers do not allow the full realisation of the public health potential of diagnosing and preventing hepatitis B and C, treating hepatitis B and curing hepatitis C. Such barriers are related to (a) lack of evidence‐based knowledge of hepatitis B and C, (b) limited access to prevention, diagnosis and treatment services with poor patient pathways, (c) declining resources and (d) the presence of social stigma and discrimination. The discussion also confirmed the emerging importance of fiscal constraints on the ability of policymakers to adequately address viral hepatitis challenges, particularly through increasing coverage of newer therapies. In Europe, it is critical that public policy bodies urgently agree on a conceptual framework for addressing the existing and emerging barriers to managing viral hepatitis. Such a framework would ensure all health systems share a common understanding of definitions and indicators and look to integrate their responses to manage policy spillovers in the most cost‐effective manner, while forging wide partnerships to sustainably and successfully address viral hepatitis.